2017
DOI: 10.5433/1679-0359.2017v38n6p3861
|View full text |Cite
|
Sign up to set email alerts
|

Animal performance, production, and quality of Tanzania grass fertilized with nitrogen

Abstract: This study aimed to assess forage production, animal performance, and the chemical composition of Tanzania grass pasture fertilized with 50, 100, 200, and 400 kg ha-1 of nitrogen. The variables analyzed were: leaf mass, daily accumulation rate, leaf/stem ratio, average daily gain, stocking rate, live weight gain per unit of area crude protein, neutral detergent fiber, and in vitro dry matter digestibility of leaves. The pasture management maintained the pasture height at 50 cm by using a continuous grazing met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…They were also higher than the range of 470 to 778 kg BW ha −1 reported in a previous study in the same area evaluating different sward heights 24 . Nitrogen fertilization also increases yield, DM digestibility, and protein content of forage, leading to higher gain per area 54 .…”
Section: Resultsmentioning
confidence: 99%
“…They were also higher than the range of 470 to 778 kg BW ha −1 reported in a previous study in the same area evaluating different sward heights 24 . Nitrogen fertilization also increases yield, DM digestibility, and protein content of forage, leading to higher gain per area 54 .…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, in temperate grasses the nitrogen supply increases the proportion of CP CC (Gierus, Pötsch, & Weichselbaum, 2016;Johnson et al, 2001), which is CP of rapid and higher digestion. This is why nitrogen fertilization in temperate grasses increases the average daily gain of animals (Pontes et al, 2018;Hernández Garay et al, 2004), while in tropical forage grasses there is a significant increase in the stocking rate (Cecato et al, 2017), which results in an increase in gain per area.…”
Section: Discussionmentioning
confidence: 99%
“…For Tanzania grass, the average values were 11.4, 11.6, 12.2, and 11.3% for IM10, IM20, IM30, and IM40. Cecato et al (2017), studying Tanzania grass in the State of Paraná observed that CP values from plants cut in the summer and autumn ranged from 9.2 to 11.0%.…”
Section: Quality Responses (Crude Protein and Fiber Yield) To Irrigat...mentioning
confidence: 99%